Innovation ecosystems in banking and monetary sector: competitiveness versus sustainability - Kubus, Renata; Mascareñas Pérez-Iñigo, Juan; González Fernández, Sara (Mercados y Negocios, 2019)
This paper addresses the innovation ecosystems configuration of the banking and monetary sector, checking its innovation orientation for competitiveness and sustainability. To achieve this objective, the actors’ perspective from the reframed Innovation Helix is applied. The main result is that the Banking and monetary authorities are rather centred on short-term system stability, which at the longer term can be counterproductive in terms of sustainability. Industry is mainly centred on competitiveness however increasingly taking into account the ‘green transition’. The society, academia and natural environment visions are strongly focused on sustainability. Currency innovations are envisaged at all the levels, bringing different proposals which can be complementary and that bring the potential of more bottom-up initiatives, collaboration and sustainability in socioecological dimension. Metamodern prospect enriches the standpoint.